STRATEGI PENGEMBANGAN INDUSTRI PAKAN IKAN AIR TAWAR DI KECAMATAN KAMPAR KABUPATEN KAMPAR - Dheryliana, M Chyntia; Rita, Iyan Yani; Deny, Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the development strategy of the freshwater fish feed industry in Kampar subdistrict of Kampar district . This study using all population of 18 units of fish feed industry as the sample by using the census method, Analysis method used in this reseatch is SWOT Analysis and IE Matrix. The results of the SWOT analysis show that the fish feed industry in Kampar District, Kampar Regency, has a strategy to develop a business in dealing with internal and external problems. IE matrix for the fish feed industry is in Column V, which has moderate internal and external capabilities and is in a state of growth and stability. Based on the SWOT analysis diagram, this strategy is in quadrant 1 (aggressive strategy). The strategy that must be established in these circumstances is to support aggressive growth policies. This aggressive strategy is more focused on SO (StrengthOpportunities) strategy, namely by using strength to take advantage of existing opportunities.Keywords: Strategy, Internal, Eksternal